Indium chloride as an electrolyte additive for primary aqueous Mg batteries. (20th March 2021) - Wang, Linqian; Snihirova, Darya; Deng, Min; Wang, Cheng; Höche, Daniel; Lamaka, Sviatlana V.; Zheludkevich, Mikhail L.
Highlights: Cell voltage and specific energy of aqueous Mg-air battery were enhanced by the addition of 10 mM InCl3 into 3.5 wt.% nacl solution. Self-corrosion reaction of Mg-0.15Ca under anodic polarization was suppressed in 1 mM Incl3 -containing electrolyte. Hydrolysis reactions of In 3+ hindered electrolyte alkalization under anodic polarization leading to better discharge activity. InCl3 addition promoted more uniform dissolution and less chunk effect of Mg-0.15Ca anode. Abstract: Indium chloride (InCl3 ) as an electrolyte additive for primary aqueous Mg batteries is evaluated in this work in terms of its effect on discharge potential, self-corrosion rate and utilization efficiency of a newly developed Mg-0.15Ca anode. InCl3 addition to aqueous electrolyte leads to a more negative discharge potential but the enhancement weakens along with the consumption of In 3+ to form In(OH)3 precipitates during the discharge process. Utilization efficiency of the anode is increased by adding InCl3 due to uniform anodic dissolution and suppressed self-corrosion with reduced chunk effect. Mg-air battery test results indicate that 10 mM InCl3 as electrolyte additive significantly enhances the cell voltage of aqueous Mg-air battery to 1.74 V and the specific energy based on anode weight loss to 2.26 kWh/ kg at 1 mA cm −2 . Graphical abstract: Image, graphical abstract